Catalyst for synthesizing pyroxasulfone, preparation method of catalyst and synthesis method of pyroxasulfone
By using a silica support supported by the primary active component V and the secondary active component M as a catalyst, the problem of process risks and low efficiency of the sulfonazole synthesis catalyst in the prior art is solved, and efficient and low-cost sulfonazole synthesis is achieved.
Patent Information
- Application Number
- CN202510123724.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The catalysts used in the prior art for the synthesis of sulfonpyrazole have problems such as high process risks, long reaction time, poor reaction effect, high cost and complex post-processing.
Using a silica support with three-dimensional dendritic channels inside, the main active component V and the secondary active component M (including at least one of Mo, Ce and Ti) is supported to form V-O-Si and M-O-Si bonds to improve the activity and efficiency of the catalyst.
The efficient synthesis of sulfonpyrazole was achieved, with the raw material conversion rate reaching 100%, and the product purity was ≥90%, reducing the preparation cost and post-treatment difficulty.
Smart Images

Figure CN119549141A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic synthesis, and in particular to a catalyst for synthesizing sulfonepyraclostrobin and a preparation method thereof, and a method for synthesizing sulfonepyraclostrobin. Background Art
[0002] Pyroxasulfone is a herbicide developed by Kumihiko Chemical and Ibara Chemical. Its common English name is Pyroxasulfone and its chemical name is 3-[5-(difluoromethoxy)-1-methyl-3-(trifluoromethyl)pyrazol-4-ylmethylsulfonyl]-4,5-dihydro-5,5-dimethyl-1,2-isoxazole. The previous synthetic routes reported so far are slightly different, but in the existing public preparation methods, the sulfide intermediates need to be oxidized to obtain pyroxasulfone. Therefore, it is particularly urgent to synthesize a highly active, long-life, highly selective catalyst that can be produced continuously.
[0003] The main catalysts for the oxidation of existing sulfide intermediates to prepare sulfonepyraclostrobin are sodium tungstate, tungsten oxide, ammonium molybdate, inorganic acids or ionic liquids, etc. However, the homogeneous reaction system using sodium tungstate as the catalyst has a large reaction exotherm and high process risk. The intermittent process using sodium tungstate and ammonium molybdate as catalysts is limited by the heat and mass transfer of the intermittent equipment itself, resulting in a long reaction time and poor reaction effect. The use of inorganic acids or ionic liquids as catalysts is costly and cannot be recycled and reused, resulting in high post-processing costs.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] The main purpose of the present application is to provide a catalyst for synthesizing sulfonepyraclostrobin and a preparation method thereof and a synthesis method of sulfonepyraclostrobin, so as to solve the problems in the prior art of using sodium tungstate, tungsten oxide, ammonium molybdate, inorganic acid or ionic liquid as catalyst to oxidize sulfide intermediates to prepare sulfonepyraclostrobin, which has at least one of high process risk, long reaction time, poor reaction effect, high cost and complex post-treatment.
[0006] In order to achieve the above-mentioned object, according to one aspect of the present application, a catalyst for synthesizing sulfonepyraclostrobin is provided, the catalyst comprising a silica carrier having a three-dimensional dendritic pore inside, the silica carrier being loaded with a main active component V and an auxiliary active component M, wherein M comprises at least one of Mo, Ce and Ti, and the specific surface area of the catalyst is 650-750m 2 / g, total pore volume is 0.8-1.3m 3 / g, and the average pore size is 5-10nm.
[0007] Furthermore, M is Ce, and in the catalyst, the molar ratio of Si, V, and Ce is 1:(0.2-0.3):(0.02-0.03).
[0008] Furthermore, M is Mo, and in the catalyst, the molar ratio of Si, V, and Mo is 1:(0.2-0.3):(0.01-0.02).
[0009] Furthermore, M is Ti, and in the catalyst, the molar ratio of Si, V, and Ti is 1:(0.2-0.3):(0.01-0.03).
[0010] Furthermore, M includes Mo and Ti, and in the catalyst, the molar ratio of Si, V, Mo and Ti is 1:(0.2-0.3):(0.01-0.02):(0.01-0.03).
[0011] Furthermore, M includes Ce, Mo and Ti, and in the catalyst, the molar ratio of Si, V, Ce, Mo and Ti is 1: (0.2-0.3): (0.02-0.03): (0.01-0.02): (0.01-0.03).
[0012] Furthermore, the catalyst is in granular form, and its particle size is 10-20 meshes.
[0013] According to the second aspect of the present application, a method for preparing the above-mentioned catalyst for synthesizing sulfonepyraclostrobin is provided, and the preparation method comprises the following steps: step S1, preparing a silica carrier having three-dimensional dendrite channels; step S2, dispersing the silica carrier in an organic alcohol and adding an alkaline solution to adjust the pH to obtain a silica suspension with a pH of 10-11; step S3, adding a V source and an M source to the silica suspension so that V and M are loaded on the silica carrier, removing the solvent, and obtaining a catalyst precursor; step S4, performing a first calcination on the catalyst precursor to obtain a catalyst for synthesizing sulfonepyraclostrobin.
[0014] Furthermore, step S1 includes: step S11, dispersing the template, surfactant and acidic solution in water to obtain solution A with a pH of 0.5-1; step S12, adding an organic solvent and an organosilicon source to solution A in sequence to obtain solution B; step S13, transferring solution B to a reactor for crystallization reaction to obtain a silica carrier precursor; step S14, performing a second calcination on the silica carrier precursor to obtain a silica carrier.
[0015] Furthermore, the template agent is selected from at least one of D,L-ammonium tartrate, pyrrolidone, cyclohexylamine and piperidine.
[0016] Furthermore, the surfactant is selected from at least one of cetyltrimethylammonium bromide, cetylpyridinium bromide and Tween 80.
[0017] Furthermore, the mass ratio of the template to the surfactant is (2-3): (2-3).
[0018] Furthermore, the acidic solution is selected from at least one of a hydrochloric acid solution and an acetic acid solution.
[0019] Furthermore, the organic solvent is selected from at least one of cyclohexane, cyclohexanol and pentanol.
[0020] Furthermore, the organic silicon source is selected from at least one of tetrabutyl orthosilicate, tetraisopropyl orthosilicate, tetraethyl orthosilicate and tetramethyl orthosilicate.
[0021] Furthermore, the mass ratio of the organosilicon source to the surfactant is 7-9:1.
[0022] Furthermore, the mass ratio of the organic solvent to water is 1:1-2.
[0023] Furthermore, the temperature of the crystallization reaction is 100-150° C., and the time of the crystallization reaction is 4-8 hours.
[0024] Furthermore, the temperature of the second calcination is 450-550° C., and the time of the second calcination is 5-6 hours.
[0025] Furthermore, in step S2, the organic alcohol is selected from at least one of methanol and ethanol.
[0026] Furthermore, the mass ratio of the silica carrier to the organic alcohol is 1:30-40.
[0027] Furthermore, the alkaline solution is selected from at least one of an aqueous ammonia solution and a sodium hydroxide solution.
[0028] Furthermore, the V source is selected from at least one of ammonium metavanadate or sodium metavanadate.
[0029] Furthermore, the M source includes at least one of a Mo source, a Ce source or a Ti source; wherein the Mo source is selected from at least one of sodium molybdate or ammonium molybdate; the Ce source is selected from at least one of cerium chloride or cerium nitrate; and the Ti source is selected from at least one of tetrabutyl titanate or tetraisopropyl titanate.
[0030] Furthermore, the temperature of the first calcination is 350-450°C, and the time of the first calcination is 3-4h. According to the third aspect of the present application, a method for synthesizing sulfonepyraclostrobin is also provided, the method comprising: an oxidation reaction of a sulfide intermediate of formula (A) with hydrogen peroxide under the action of a catalyst to obtain sulfonepyraclostrobin. The schematic diagram of the synthesis of sulfonepyraclostrobin is as follows:
[0031]
[0032] Wherein, the catalyst is the catalyst provided in the first aspect or the catalyst obtained according to the preparation method provided in the second aspect.
[0033] Further, the catalyst is loaded in a fixed bed, and the temperature of the oxidation reaction is 60-65°C.
[0034] By applying the technical solution of the present application, the catalyst for synthesizing sulfonepyraclostrobin provided by the present application is composed of silica with a large specific surface area, a large pore volume, and three-dimensional dendritic channels inside as a carrier, and a main active component V and an auxiliary active component M are introduced to cooperate with each other, so that the metal V and M form VO-Si and MO-Si bonds with the carrier, thereby easily forming nano-scale microcrystals embedded in the surface of the silica, and the lattice oxygen in the bridging oxygen atom can improve the activity of the catalyst, which is more conducive to the oxidation of the sulfide group to sulfone.
[0035] The catalyst provided in the present application is used in the synthesis of sulfonepyraclostrobin, the raw material conversion rate reaches 100%, and the product purity is ≥90%, which effectively reduces the preparation cost and post-processing difficulty of sulfonepyraclostrobin, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0037] Figure 1 The XRD pattern of the silica carrier prepared in Example 1 of the present application is shown;
[0038] Figure 2 The SEM image of the silica carrier prepared in Example 1 of the present application is shown;
[0039] Figure 3 The TEM image of the silica carrier prepared in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0041] As analyzed in the background technology of this application, the main catalysts for the oxidation of existing sulfide intermediates to prepare sulfonepyraclostrobin are sodium tungstate, tungsten oxide, ammonium molybdate, inorganic acids or ionic liquids, etc., but the homogeneous reaction system using sodium tungstate as a catalyst has a large reaction exotherm and high process risk; the intermittent process using sodium tungstate and ammonium molybdate as catalysts is limited by the heat transfer and mass transfer of the intermittent equipment itself, the reaction time is long, and the reaction effect is poor; the use of inorganic acids or ionic liquids as catalysts is costly, and cannot be recycled and reused, and the post-processing cost is high. In order to solve at least one of the above problems, the present application provides a catalyst for synthesizing sulfonepyraclostrobin and a preparation method thereof and a method for synthesizing sulfonepyraclostrobin.
[0042] In a first typical embodiment of the present application, a catalyst for synthesizing sulfonepyraclostrobin is provided, which comprises a silica carrier having a three-dimensional dendritic pore inside, the silica carrier being loaded with a main active component V and an auxiliary active component M, wherein M comprises at least one of Mo, Ce and Ti; and the specific surface area of the catalyst is 650-750 m 2 / g, with a total pore volume of 0.8-1.3cm 3 / g, and the average pore size is 5-10nm.
[0043] The catalyst for synthesizing sulfonepyraclostrobin provided in the present application is composed of silica with a large specific surface area, a large pore volume, and three-dimensional dendritic channels inside as a carrier, and introduces a main active component V and an auxiliary active component M to cooperate with each other, so that the metal V and M form VO-Si and MO-Si bonds with the carrier, thereby easily forming nano-scale microcrystals embedded in the surface of the silica, and the lattice oxygen in the bridging oxygen atom can improve the activity of the catalyst, which is more conducive to the oxidation of the sulfide group to sulfone.
[0044] The catalyst provided in the present application is used in the reaction of synthesizing sulfonepyraclostrobin, and the raw material conversion rate reaches 100%, and the product purity is ≥90%, which effectively reduces the preparation cost and post-processing difficulty of sulfonepyraclostrobin, and has broad application prospects.
[0045] Typically, but not limiting, the specific surface area of the catalyst for synthesizing sulfonepyraclostrobin provided in the present application can be 650 m 2 / g, 660 m 2 / g, 680 m 2 / g, 690 m 2 / g, 696.5 m 2 / g, 700 m 2 / g, 701.6 m 2 / g, 715 m 2 / g、718m 2 / g, 718.96 m 2 / g, 719.04 m2 / g, 720 m 2 / g, 750 m 2 / g or a range of any two values; the total pore volume is 0.8 cm 3 / g, 0.84 cm 3 / g, 0.88 cm 3 / g, 0.90 cm 3 / g, 0.91 cm 3 / g, 0.916 cm 3 / g, 0.93 cm 3 / g, 0.95 cm 3 / g, 0.98 cm 3 / g, 0.99 cm 3 / g, 1.0 cm 3 / g, 1.036 cm 3 / g, 1.10 cm 3 / g, 1.15 cm 3 / g, 1.20 cm 3 / g, 1.221 cm 3 / g, 1.25 cm 3 / g, 1.30 cm 3 / g, or a range consisting of any two values; the average pore size is 5.0nm, 5.5nm, 6.0nm, 6.5nm, 7.0nm, 7.5nm, 8.0nm, 8.5nm, 9.0nm, 9.5nm, 10nm, or a range consisting of any two values.
[0046] In some embodiments, M is Ce, and the molar ratio of Si, V, and Ce in the catalyst is 1:(0.2-0.3):(0.02-0.03).
[0047] In some embodiments, M is Mo, and the molar ratio of Si, V, and Mo in the catalyst is 1:(0.2-0.3):(0.01-0.02).
[0048] In some embodiments, M is Ti, and the molar ratio of Si, V, and Ti in the catalyst is 1:(0.2-0.3):(0.01-0.03).
[0049] In some embodiments, M includes Mo and Ti, and in the catalyst, the molar ratio of Si, V, Mo, and Ti is 1:(0.2-0.3):(0.01-0.02):(0.01-0.03).
[0050] In some embodiments, M includes Ce, Mo and Ti. In the catalyst for synthesizing sulfonepyraclostrobin provided in the present application, the molar ratio of Si, V, Ce, Mo and Ti is 1: (0.2-0.3): (0.02-0.03): (0.01-0.02): (0.01-0.03).
[0051] In the catalyst for synthesizing sulfonepyraclostrobin provided in the present application, taking the molar amount of Si in the catalyst as 1.0, the molar amount of V is 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30 or a range consisting of any two numerical values; the molar amount of Ti is 0.01, 0.012, 0.015, 0.018, 0.02, 0.022, 0.025, 0.028, 0.03 or a range consisting of any two numerical values; the molar amount of Mo is 0.01, 0.012, 0.015, 0.018, 0.02 or a range consisting of any two numerical values; the molar amount of Ce is 0.02, 0.022, 0.025, 0.028, 0.03 or a range consisting of any two numerical values.
[0052] In order to facilitate the loading of the catalyst provided in the present application into a fixed bed for the continuous synthesis of sulfonepyraclostrobin, in some embodiments, the catalyst for synthesizing sulfonepyraclostrobin provided in the present application is granular, and its particle size is 10-20 mesh, such as 10 mesh, 12 mesh, 15 mesh, 18 mesh, 20 mesh or a range value composed of any two numerical values.
[0053] In a second typical embodiment of the present application, a method for preparing the catalyst of sulfonepyraclostrobin provided in the above-mentioned first typical embodiment is provided, and the preparation method comprises the following steps: step S1, preparing a silica carrier having three-dimensional dendritic channels; step S2, dispersing the silica carrier in an organic alcohol solvent and adding an alkaline solution to adjust the pH to obtain a silica suspension with a pH of 10-11; step S3, adding a V source and an M source to the silica suspension so that V and M are loaded on the silica carrier, removing the solvent, and obtaining a catalyst precursor; step S4, performing a first calcination on the catalyst precursor to obtain a catalyst.
[0054] The preparation method of the catalyst of sulfonepyraclostrobin provided in the present application has a simple process and is easy to operate, which is conducive to large-scale production and thus reduces production costs.
[0055] In the above step S2, the pH of the silicon dioxide suspension can be 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9, 11 or a range consisting of any two values.
[0056] In some embodiments, the above step S1 includes: step S11, dispersing the template, surfactant and acidic solution in water to obtain solution A with a pH of 0.5-1; step S12, adding an organic solvent and an organosilicon source to solution A in sequence to obtain solution B; step S13, transferring solution B to a reactor for crystallization reaction to obtain a silica carrier precursor; step S14, performing a second calcination on the silica carrier precursor to obtain a silica carrier.
[0057] The pH of the solution A may be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0 or a range consisting of any two values.
[0058] The template agent is a commonly used template agent in the art, including but not limited to any one or more of D, L-ammonium tartrate, pyrrolidone, cyclohexylamine, and piperidine, preferably D, L-ammonium tartrate, which is more conducive to improving the preparation efficiency.
[0059] The above-mentioned surfactant is a commonly used surfactant in the art, including but not limited to any one or more of cetyltrimethylammonium bromide, cetylpyridinium bromide, and Tween 80.
[0060] The above-mentioned acidic solution is an acidic solution commonly used in the art to adjust the pH value, including but not limited to a mixed solution of one or both of a hydrochloric acid solution or an acetic acid solution. Preferably, a hydrochloric acid solution is more conducive to avoiding the introduction of impurity ions, and more preferably, a hydrochloric acid solution with a mass concentration of 35-40%.
[0061] The above organic solvent is a commonly used organic solvent in the art, including but not limited to any one of cyclohexane, cyclohexanol or pentanol or a mixed solution of two or more solvents.
[0062] The above-mentioned organic silicon source is a silicon source commonly used in the art to prepare silicon dioxide, including but not limited to any one or more of tetrabutyl orthosilicate, tetraisopropyl orthosilicate, tetraethyl orthosilicate, and tetramethyl orthosilicate, preferably tetraisopropyl orthosilicate or tetraethyl orthosilicate.
[0063] In order to further prepare a silica carrier with large pore volume, large specific surface area and uniform pore particle size, in some embodiments, the mass ratio of the organosilicon source to the surfactant is 7-9:1, such as 7.2:1, 7.4:1, 7.6:1, 7.8:1, 8:1, 8,2:1, 8.4:1, 8.6:1, 8.8:1, 9:1 or a range of any two values. In some embodiments, the mass ratio of the organic solvent to water is 1:1-2 (such as 1:1, 1:1.1, 1:1.2, 1:1.5, 1:1.8, 1:2.0), and more preferably 1:1.
[0064] In order to further improve the efficiency of the crystallization reaction, the crystallization reaction temperature is preferably 100-150°C, and the crystallization reaction time is 4-8h. The crystallization reaction temperature is, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or a range consisting of any two values; the crystallization reaction time is, for example, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or a range consisting of any two values.
[0065] In the above step S13, after the crystallization reaction is completed, a crystallization product mixed solution is obtained, and the crystallization product mixed solution is solid-liquid separated, and then washed with deionized water and dried to obtain a silica carrier precursor. The above solid-liquid separation method is preferably filtration.
[0066] In order to further improve the preparation efficiency of the silicon oxide carrier, the second calcination temperature is preferably 450-550°C, and the second calcination time is preferably 5-6h. The second calcination temperature is 450°C, 480°C, 500°C, 520°C, 550°C, or a range consisting of any two values; the second calcination time is 5h, 5.2h, 5.5h, 5.8h, 6h, or a range consisting of any two values.
[0067] In some embodiments, the heating rate of the silica precursor to the second calcination temperature is 5-15°C / min (e.g., 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min) to facilitate more uniform pore channels and pore volume of the silica carrier.
[0068] In the above step S2, the organic alcohol solution is used to disperse the silica carrier. From the perspective of environmental protection and dispersion efficiency, the organic alcohol is preferably selected from a mixed solution of any one or more of methanol or ethanol.
[0069] In order to further improve the preparation efficiency of the silica suspension, the mass ratio of the silica carrier to the organic alcohol is preferably 1:30-40, such as 1:30, 1:32, 1:35, 1:38, 1:40 or a range consisting of any two values.
[0070] The alkaline solution is used to adjust the pH of the silica suspension to 10-11, and any alkaline solution commonly used in the art can be used, including but not limited to at least one of an aqueous ammonia solution or a sodium hydroxide solution. In order to further reduce the introduction of impurities, the alkaline solution is preferably an aqueous ammonia solution, and more preferably an aqueous ammonia solution with a mass concentration of 20-30%.
[0071] In some embodiments, the aqueous ammonia solution is added to the organic alcohol solution of the silica carrier by dropwise addition, and the time for dropwise addition of the aqueous ammonia solution is controlled within 3-5 minutes.
[0072] In the above step S3, the above V source is a V salt commonly used in the art, including but not limited to a mixture of any one or more of ammonium metavanadate or sodium metavanadate.
[0073] The above-mentioned M source includes any one or more of a Mo source, a Ce source and a Ti source; wherein the Mo source includes but is not limited to any one or more of sodium molybdate or ammonium molybdate; the Ce source is selected from any one or more of cerium chloride or cerium nitrate; the Ti source includes but is not limited to any one or more of tetrabutyl titanate or tetraisopropyl titanate.
[0074] In the above step S3, the method of removing the solvent includes but is not limited to heating to remove the organic alcohol and the solvents and impurities such as water or ammonia introduced by the alkaline solution. In some embodiments, heating to 75-85° C. is used to facilitate the removal of the solvent and impurities.
[0075] In order to further improve the preparation efficiency of the catalyst, the first calcination temperature is preferably 350-450°C, and the first calcination time is preferably 3-4h. Specifically, the first calcination temperature is 350°C, 380°C, 400°C, 420°C, 450°C, or a range consisting of any two values; the first calcination time is 3h, 3.2h, 3.5h, 3.8h, 4h, or a range consisting of any two values.
[0076] In some embodiments, preferably, step S4 is to first dry the catalyst precursor and then perform a first calcination.
[0077] Specifically, the catalyst precursor is first dried at 80-100° C. for 6-8 hours, and then heated to a first calcination temperature at a rate of 5° C.-15° C. / min for calcination.
[0078] In some embodiments, in order to facilitate loading the above catalyst into a fixed bed for continuous synthesis of sulfonepyraclostrobin, the above step S4 further includes tableting and crushing the catalyst in sequence to obtain a catalyst with an average particle size of 10-20 mesh.
[0079] In a third typical embodiment of the present application, a method for synthesizing sulfonepyraclostrobin is also provided, the method comprising: subjecting a sulfide intermediate to an oxidation reaction with hydrogen peroxide in the presence of a catalyst to obtain sulfonepyraclostrobin, wherein the schematic diagram of the synthesis of sulfonepyraclostrobin is as follows:
[0080]
[0081] The catalyst is the catalyst provided in the first typical embodiment or the catalyst obtained according to the preparation method provided in the second typical embodiment.
[0082] The method for synthesizing sulfonepyraclostrobin provided in the present application comprises loading the above-mentioned catalyst on a fixed bed, and then respectively introducing a sulfide intermediate and hydrogen peroxide into the fixed bed, so that the sulfide intermediate and hydrogen peroxide are catalyzed by the catalyst to generate sulfonepyraclostrobin, and not only the raw material conversion rate can reach 100%, but also the product purity is ≥90%, thereby realizing the continuous synthesis of sulfonepyraclostrobin and being more conducive to reducing production costs.
[0083] In addition, the present application uses silicon dioxide with three-dimensional dendritic channels as a carrier, and the rich channels inside the silicon dioxide can better disperse the main active components and auxiliary active components on the channel surface of the silicon dioxide, thereby improving the metal dispersion of the main active components. The improvement of dispersion greatly improves its atomic utilization, reduces the input amount of active components, and thus reduces the cost of catalyst preparation. The catalyst provided by the present application can be directly applied to a continuous fixed bed, eliminating the influence of unfavorable factors such as heat transfer, mass transfer, and long reaction time, and the safety and production capacity of the process will be greatly improved.
[0084] In some embodiments, the temperature of the oxidation reaction is 60-65°C, the reaction is mild, and it is more conducive to process control. The catalyst is loaded in a fixed bed and can be used continuously.
[0085] In some specific embodiments, when a fixed bed is used for the continuous preparation of sulfonepyraclostrobin, an acetonitrile solution of a thioether intermediate (the mass ratio of acetonitrile to the thioether intermediate is 3:1) with a flow rate of 0.5 g / min is passed into the fixed bed, and a hydrogen peroxide solution (mass concentration of 50%) with a flow rate of 0.1 g / min is passed into the fixed bed, and an overflow reaction form is adopted.
[0086] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0087] Example 1
[0088] This embodiment provides a catalyst, which includes a silica carrier having three-dimensional dendritic channels inside, the silica carrier is loaded with a main active component V and an auxiliary active component Ce, and the molar ratio of Si, V and Ce is 1:0.2:0.02.
[0089] The catalyst is prepared according to the following steps:
[0090] (1) Preparation of silica carrier with three-dimensional dendritic channels
[0091] (1.1) Weigh 25 g of D,L-ammonium tartrate, 25 g of hexadecyltrimethylammonium bromide (CTAB), and 125 g of hydrochloric acid, dissolve in 1400 mL of deionized water, and stir at room temperature until completely dissolved to obtain solution A with a pH of 0.7.
[0092] (1.2) Add 1330 mL of cyclohexane and 70 mL of pentanol to the above solution A, stir vigorously at room temperature for 30 minutes, slowly add 200 g of tetraethyl orthosilicate dropwise, and continue stirring at room temperature for 25-30 minutes to obtain solution B;
[0093] (1.3) Transfer solution B to a sealed polytetrafluoroethylene autoclave and heat at 120°C for 5 hours to perform a crystallization reaction. After the crystallization reaction is completed, filter and separate, wash the crystallized product with deionized water, and dry it in a drying oven at 80°C for 5 hours to obtain a silica carrier precursor;
[0094] (1.4) The silica carrier precursor was calcined in air at 550 °C for 5 h at a heating rate of 5 °C / min and ground to obtain a white silica carrier.
[0095] (2) 40 g of a silica carrier was placed in a round-bottom flask containing 1200 g of ethanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt % of ammonia water was added dropwise (within 3 minutes) to the stirred solution to obtain a silica suspension with a pH of 11.
[0096] (3) Then, 15.6 g of ammonium metavanadate, 4.35 g of cerium nitrate and 5 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution. The mixed solution was heated to 80° C. to evaporate ethanol and ammonia to obtain a catalyst precursor.
[0097] (4) After the catalyst precursor is dried at 100 °C for 8 hours, the solid product is placed in a muffle furnace at 400 °C and calcined for 4 hours at a heating rate of 5 °C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0098] Example 2
[0099] This embodiment provides a catalyst, which includes a silica carrier having three-dimensional dendritic channels inside, the silica carrier is loaded with a main active component V and an auxiliary active component Mo, and the molar ratio of Si, V and Mo is 1:0.3:0.015.
[0100] The catalyst is prepared according to the following steps:
[0101] (1) Preparation of silica carrier with three-dimensional dendritic channels
[0102] (1.1) Weigh 20 g of D,L-ammonium tartrate, 30 g of Tween 80 and 120 g of hydrochloric acid, dissolve in 1200 mL of deionized water, and stir at room temperature until completely dissolved to obtain solution A with a pH of 0.5;
[0103] (1.2) Add 1330 mL of cyclohexane and 70 mL of pentanol to the above solution A, stir vigorously at room temperature for 30 minutes, slowly add 250 g of tetraisopropyl orthosilicate dropwise, and continue stirring at room temperature for 25-30 minutes to obtain solution B;
[0104] (1.3) Transfer solution B to a sealed polytetrafluoroethylene autoclave and heat at 150°C for 4 hours to perform a crystallization reaction. After the crystallization reaction is completed, filter and separate, wash the crystallized product with deionized water, and dry it in a drying oven at 90°C for 4 hours to obtain a silica carrier precursor;
[0105] (1.4) The silica carrier precursor was calcined in air at 550 °C for 5 hours at a heating rate of 15 °C / min and ground to obtain a white silica carrier.
[0106] (2) 40 g of a silica carrier was placed in a round-bottom flask containing 1600 g of ethanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt % of ammonia water was added dropwise (within 5 minutes) to the stirred solution to obtain a silica suspension with a pH of 10.
[0107] (3) Then, 23.4 g of ammonium metavanadate, 1.96 g of ammonium molybdate and 10 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution. The mixed solution was heated to 80° C. to evaporate ethanol and ammonia to obtain a catalyst precursor.
[0108] (4) After the catalyst precursor is dried at 80°C for 8 hours, the solid product is placed in a muffle furnace at 450°C and calcined for 3 hours at a heating rate of 10°C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0109] Example 3
[0110] This embodiment provides a catalyst, which includes a silica carrier with three-dimensional dendritic channels inside, the silica carrier is loaded with a main active component V and auxiliary active components Mo and Ti, and the molar ratio of Si, V, Mo and Ti is 1:0.2:0.015:0.02.
[0111] The catalyst is prepared according to the following steps:
[0112] (1) Preparation of silica carrier with three-dimensional dendritic channels
[0113] (1.1) Weigh 30 g of D,L-ammonium tartrate, 25 g of cetylpyridinium bromide (CPB), and 110 g of hydrochloric acid, dissolve in 1150 mL of deionized water, and stir at room temperature until completely dissolved to obtain solution A with a pH of 1.
[0114] (1.2) Add 1050 mL of cyclohexane, 30 mL of pentanol and 70 mL of cyclohexanol to the above solution A, stir vigorously at room temperature for 30 minutes, slowly dropwise add 220 g of tetraisopropyl orthosilicate, and continue stirring at room temperature for 25-30 minutes to obtain solution B;
[0115] (1.3) Transfer solution B to a sealed polytetrafluoroethylene autoclave and heat at 120°C for 6 hours to perform a crystallization reaction. After the crystallization reaction is completed, filter and separate, wash the crystallized product with deionized water, and dry it in a drying oven at 85°C for 5 hours to obtain a silica carrier precursor;
[0116] (1.4) The silica carrier precursor was calcined in air at 500 °C for 6 h at a heating rate of 12 °C / min and ground to obtain a white silica carrier.
[0117] (2) 40 g of a silica carrier was placed in a round-bottom flask containing 1500 g of ethanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt % of ammonia water was added dropwise (within 3 minutes) to the stirred solution to obtain a silica suspension with a pH of 11.
[0118] (3) Then, 15.6 g of ammonium metavanadate, 1.96 g of ammonium molybdate, 4.54 g of tetrabutyl titanate and 10 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution. The mixed solution was heated to 85° C. to evaporate ethanol and ammonia to obtain a catalyst precursor.
[0119] (4) After the catalyst precursor is dried at 80°C for 7 hours, the solid product is placed in a muffle furnace at 450°C and calcined for 3 hours at a heating rate of 10°C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0120] Example 4
[0121] This embodiment provides a catalyst, which includes a silica carrier with three-dimensional dendritic channels inside, the silica carrier is loaded with a main active component V and auxiliary active components Ce, Mo and Ti, and the molar ratio of Si, V, Ce, Mo and Ti is 1:0.27:0.01:0.01:0.01.
[0122] The catalyst is prepared according to the following steps:
[0123] (1) Preparation of silica carrier with three-dimensional dendritic channels
[0124] (1.1) Weigh 30 g of D,L-ammonium tartrate, 30 g of cetylpyridinium bromide (CPB), and 130 g of hydrochloric acid, dissolve in 1400 mL of deionized water, and stir at room temperature until completely dissolved to obtain solution A with a pH of 0.6.
[0125] (1.2) Add 1300 mL of cyclohexane and 100 mL of cyclohexanol to the above solution A, stir vigorously at room temperature for 30 minutes, slowly add 220 g of tetraethyl orthosilicate dropwise, and continue stirring at room temperature for 25-30 minutes to obtain solution B;
[0126] (1.3) Transfer solution B to a sealed polytetrafluoroethylene autoclave and heat at 120°C for 6 hours to perform a crystallization reaction. After the crystallization reaction is completed, filter and separate, wash the crystallized product with deionized water, and dry it in a drying oven at 85°C for 5 hours to obtain a silica carrier precursor;
[0127] (1.4) The silica carrier precursor was calcined in air at 500 °C for 6 h at a heating rate of 12 °C / min and ground to obtain a white silica carrier.
[0128] (2) 40 g of a silica carrier was placed in a round-bottom flask containing 1400 g of methanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt % of ammonia water was added dropwise (3 minutes) to the stirred solution to obtain a silica suspension with a pH of 11.
[0129] (3) Then, 22 g of sodium metavanadate, 1.64 g of cerium chloride, 1.5 g of sodium molybdate, 1.89 g of tetraisopropyl titanate and 10 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution, and the mixed solution was heated to 85° C. to evaporate ethanol and ammonia to obtain a catalyst precursor.
[0130] (4) After the catalyst precursor is dried at 80°C for 7 hours, the solid product is placed in a muffle furnace at 450°C and calcined for 3 hours at a heating rate of 10°C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0131] Example 5
[0132] The difference between this embodiment and embodiment 1 is that in step (1.3), the amount of hexadecyltrimethylammonium bromide used is 23 g, the temperature of the crystallization reaction is 110° C., and the time of the crystallization reaction is 4 h.
[0133] Example 6
[0134] The difference between this embodiment and embodiment 1 is that in step (1.3), the amount of hexadecyltrimethylammonium bromide used is 25 g, the temperature of the crystallization reaction is 150° C., and the time of the crystallization reaction is 8 h.
[0135] Example 7
[0136] The difference between this embodiment and embodiment 1 is that in step (3), the amount of ammonium metavanadate used is 15.6 g, and the amount of cerium nitrate used is 6.52 g.
[0137] Example 8
[0138] The difference between this embodiment and embodiment 1 is that in step (3), the amount of ammonium metavanadate used is 23.4 g, and the amount of cerium nitrate used is 4.35 g.
[0139] Example 9
[0140] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium metavanadate used is 23.4 g, and the amount of ammonium molybdate used is 1.3 g.
[0141] Example 10
[0142] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium metavanadate used is 15.6 g, and the amount of ammonium molybdate used is 2.6 g.
[0143] Embodiment 11
[0144] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium metavanadate used is 15.6 g, the amount of ammonium molybdate used is 2.6 g, and the amount of tetrabutyl titanate used is 2.3 g.
[0145] Example 12
[0146] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium metavanadate used is 23.4 g, the amount of ammonium molybdate used is 1.3 g, and the amount of tetrabutyl titanate used is 6.8 g.
[0147] Embodiment 13
[0148] The difference between this embodiment and embodiment 3 is that in step (3), the amount of ammonium metavanadate used is 23.4 g, and the amount of tetrabutyl ester used is 2.3 g.
[0149] Embodiment 14
[0150] The difference between this embodiment and embodiment 3 is that in step (3), the amount of ammonium metavanadate used is 15.6 g, and the amount of tetrabutyl titanate used is 6.8 g.
[0151] Embodiment 15
[0152] The difference between this embodiment and embodiment 4 is that in step (3), the amount of sodium metavanadate used is 16.3 g, the amount of cerium chloride used is 4.9 g, the amount of sodium molybdate used is 1.4 g, and the amount of tetraisopropyl titanate used is 5.7 g.
[0153] Example 16
[0154] The difference between this embodiment and embodiment 4 is that in step (3), the amount of ammonium metavanadate used is 23.4 g, the amount of cerium chloride used is 3.3 g, the amount of sodium molybdate used is 2.7 g, and the amount of tetraisopropyl titanate used is 1.9 g.
[0155] Embodiment 17
[0156] The difference between this embodiment and embodiment 1 is that in step (3), the amount of cerium chloride used is 2.5 g.
[0157] Embodiment 18
[0158] The difference between this embodiment and embodiment 1 is that in step (3), the amount of cerium chloride used is 6.6 g.
[0159] Embodiment 19
[0160] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium molybdate used is 0.65 g.
[0161] Embodiment 20
[0162] The difference between this embodiment and embodiment 2 is that in step (3), the amount of ammonium molybdate used is 3.9 g.
[0163] Embodiment 21
[0164] The difference between this embodiment and embodiment 3 is that in step (3), the amount of ammonium metavanadate used is 15.6 g, and the amount of tetrabutyl titanate used is 1.1 g.
[0165] Embodiment 22
[0166] The difference between this embodiment and embodiment 4 is that in step (3), the amount of sodium metavanadate used is 22 g, and the amount of tetrabutyl titanate used is 0.9 g.
[0167] Comparative Example 1
[0168] This comparative example provides a catalyst comprising a silica carrier and an active component V and auxiliary active components Ce, Mo and Ti supported on the silica carrier, and the molar ratio of Si, V, Ce, Mo and Ti is 1: 0.27: 0.01: 0.01: 0.01.
[0169] It is prepared according to the following steps:
[0170] (1) 40 g of a commercial silica carrier (purchased from Innochem, model A26027) was placed in a round-bottom flask containing 1400 g of methanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt% ammonia water was added dropwise to the stirred solution (3 minutes) to obtain a silica suspension with a pH of 11.
[0171] (2) Then, 22 g of sodium metavanadate, 1.64 g of cerium chloride, 1.5 g of sodium molybdate, 1.89 g of tetraisopropyl titanate and 10 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution, and the mixed solution was heated to 85° C. to evaporate ethanol and ammonia to obtain a catalyst precursor.
[0172] (3) After the catalyst precursor is dried at 80°C for 7 hours, the solid product is placed in a muffle furnace at 450°C and calcined for 3 hours at a heating rate of 10°C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0173] Comparative Example 2
[0174] This comparative example provides a catalyst comprising a silica carrier and an active component V and auxiliary active components Ce, Mo and Ti supported on the silica carrier, and the molar ratio of Si, V, Ce, Mo and Ti is 1:0.3:0:0.015:0.
[0175] It is prepared according to the following steps:
[0176] (1) 40 g of a commercial silica carrier (purchased from Innochem, model A26027) was placed in a round-bottom flask containing 1600 g of methanol. The silica carrier suspension was dispersed by ultrasonic treatment for 15-20 minutes, and then stirred at room temperature for 5-10 minutes. 25 wt% ammonia water was added dropwise to the stirred solution (5 minutes) to obtain a silica suspension with a pH of 10.
[0177] (2) Then, 23.4 g of sodium metavanadate, 1.96 g of ammonium molybdate and 10 ml of deionized water were added to the silica suspension under stirring at room temperature to obtain a mixed solution, and the mixed solution was heated to 80° C. to evaporate methanol and ammonia to obtain a catalyst precursor.
[0178] (3) After the catalyst precursor is dried at 80°C for 7 hours, the solid product is placed in a muffle furnace at 450°C and calcined for 3 hours at a heating rate of 10°C / min to obtain a block catalyst. The block catalyst is simply pressed into tablets by a tablet press and crushed into 10-20 mesh to obtain the aforementioned catalyst.
[0179] Test Example 1
[0180] The silica carrier obtained in step (1.4) of Example 1 was subjected to XRD test, and the results were as follows: Figure 1 As shown, from Figure 1 It can be seen that the synthesized carrier is mesoporous silica and has order (the pore size can be calculated using the Bragg formula in combination with the peak angle of the XRD pattern to be mesoporous).
[0181] The catalyst provided in Example 1 was subjected to SEM and TEM tests. The results are as follows: Figure 2 and Figure 3 As shown, from Figure 2 and Figure 3 It can be seen that the catalyst is spherical, and there are wrinkles and pores on the surface of the spherical catalyst, which indicates that the interior of the carbon dioxide carrier has a three-dimensional dendritic pore structure.
[0182] Test Example 2
[0183] The specific surface area, total pore volume and average pore diameter of the catalysts provided in the above examples and comparative examples were measured, and the results are shown in Table 1 below.
[0184] 40 g of the catalysts provided in the above examples and comparative examples were respectively filled in a fixed bed, and the sulfide intermediate ( ) acetonitrile solution (the mass ratio of acetonitrile to sulfide intermediates is 3:1) is introduced into the fixed bed at a rate of 0.5 g / min, and a hydrogen peroxide solution (mass concentration is 50%) is introduced into the fixed bed at a rate of 0.1 g / min for continuous oxidation at 60°C, and a sulfonepyraclostrobin reaction solution is obtained in the form of overflow reaction. The conversion rate of sulfide intermediates and the selectivity of sulfonepyraclostrobin are determined, and the results are shown in Table 1.
[0185] Among them, (1) the catalyst specific surface area, total pore volume and average pore diameter were measured using the BSD-660SA3S equipment of Beijing Best Instrument Co., Ltd.
[0186] (2) The conversion rate of sulfide intermediates is determined as follows: Conversion rate (%) = (number of moles of sulfide intermediates in 1-sulfonepyraclostrobin reaction solution / number of moles of sulfide intermediates input)*100% (3) The purity of 1-sulfonepyraclostrobin is determined by high performance liquid chromatography.
[0187] Table 1
[0188]
[0189] From the above description, it can be seen that the above-mentioned embodiments of the present application achieve the following technical effects: applying the technical scheme of the present application, the catalyst for synthesizing sulfonepyraclostrobin provided by the present application is composed of silica with a large specific surface area, a large pore volume, and three-dimensional dendritic channels inside as a carrier, and the main active component V and the auxiliary active component M are introduced to cooperate with each other, so that the metal V and M form VO-Si and MO-Si bonds with the carrier, thereby easily forming nano-scale microcrystals embedded in the surface of the silica, and the lattice oxygen in the bridging oxygen atom can improve the activity of the catalyst, which is more conducive to the oxidation of the sulfide group to sulfone.
[0190] The catalyst provided in the present application is used in the synthesis of sulfonepyraclostrobin, the raw material conversion rate reaches 100%, and the product purity is ≥90%, which effectively reduces the preparation cost and post-processing difficulty of sulfonepyraclostrobin, and has broad application prospects.
[0191] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A catalyst for synthesizing sulfonepyraclostrobin, characterized in that: The catalyst comprises a silica carrier having three-dimensional dendritic channels inside, the silica carrier is loaded with a main active component V and an auxiliary active component M, wherein M comprises at least one of Mo, Ce and Ti; and the specific surface area of the catalyst is 650-750m 2 / g, total pore volume is 0.8-1.3m 3 / g, and the average pore size is 5-10nm.
2. The catalyst according to claim 1, characterized in that In the catalyst, M is Ce, and in the catalyst, the molar ratio of Si, V, and Ce is 1: (0.2-0.3): (0.02-0.03); and / or, the M is Mo, and in the catalyst, the molar ratio of Si, V, and Mo is 1:(0.2-0.3):(0.01-0.02); And / or, M is Ti, and in the catalyst, the molar ratio of Si, V, and Ti is 1: (0.2-0.3): (0.01-0.03).
3. The catalyst according to claim 1, characterized in that The M includes Mo and Ti, and in the catalyst, the molar ratio of Si, V, Mo, and Ti is 1: (0.2-0.3): (0.01-0.02): (0.01-0.03); And / or, the M includes Ce, Mo and Ti, and in the catalyst, the molar ratio of Si, V, Ce, Mo and Ti is 1: (0.2-0.3): (0.02-0.03): (0.01-0.02): (0.01-0.03).
4. The catalyst according to any one of claims 1 to 3, characterized in that The catalyst is in granular form, and its particle size is 10-20 meshes.
5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step S1, preparing a silica carrier having three-dimensional dendritic channels; Step S2, dispersing the silica carrier in an organic alcohol and adding an alkaline solution to adjust the pH to obtain a silica suspension with a pH of 10-11; Step S3, adding a V source and an M source to the silica suspension so that V and M are loaded on the silica carrier, and removing the solvent to obtain a catalyst precursor; Step S4, performing a first calcination on the catalyst precursor to obtain the catalyst.
6. The method for preparing the catalyst according to claim 5, characterized in that: The step S1 comprises: Step S11, dispersing the template, surfactant and acidic solution in water to obtain a solution A with a pH of 0.5-1; Step S12, adding an organic solvent and an organic silicon source to solution A in sequence to obtain solution B; Step S13, transferring solution B to a reactor for crystallization reaction to obtain a silica carrier precursor; Step S14, performing a second calcination on the silica carrier precursor to obtain the silica carrier.
7. The method for preparing a catalyst according to claim 6, characterized in that: The template agent is selected from at least one of D,L-ammonium tartrate, pyrrolidone, cyclohexylamine, and piperidine; And / or, the surfactant is selected from at least one of cetyltrimethylammonium bromide, cetylpyridinium bromide and Tween 80; and / or, the mass ratio of the template to the surfactant is (2-3): (2-3); And / or, the acidic solution is selected from at least one of a hydrochloric acid solution and an acetic acid solution; And / or, the organic solvent is selected from at least one of cyclohexane, cyclohexanol and pentanol; And / or, the organic silicon source is selected from at least one of tetrabutyl orthosilicate, tetraisopropyl orthosilicate, tetraethyl orthosilicate and tetramethyl orthosilicate; And / or, the mass ratio of the organosilicon source to the surfactant is 7-9:1; And / or, the mass ratio of the organic solvent to the water is 1:1-2; And / or, the temperature of the crystallization reaction is 100-150° C., and the time of the crystallization reaction is 4-8 hours; And / or, the temperature of the second calcination is 450-550° C., and the time of the second calcination is 5-6 hours.
8. The method for preparing the catalyst according to claim 5, characterized in that: In step S2, the organic alcohol is selected from at least one of methanol and ethanol; And / or, the mass ratio of the silica carrier to the organic alcohol is 1:30-40; And / or, the alkaline solution is selected from at least one of an aqueous ammonia solution or a sodium hydroxide solution; And / or, the V source is selected from at least one of ammonium metavanadate or sodium metavanadate; And / or, the M source includes at least one of a Mo source, a Ce source or a Ti source; wherein the Mo source is selected from at least one of sodium molybdate or ammonium molybdate; the Ce source is selected from at least one of cerium chloride or cerium nitrate; the Ti source is selected from at least one of tetrabutyl titanate or tetraisopropyl titanate; And / or, the temperature of the first calcination is 350-450° C., and the time of the first calcination is 3-4 hours.
9. A method for synthesizing sulfonepyraclostrobin, characterized in that: The synthesis method comprises: an oxidation reaction of a sulfide intermediate of formula (A) and hydrogen peroxide under the action of a catalyst to obtain the sulfonepyraclostrobin. The synthesis schematic diagram of the sulfonepyraclostrobin is as follows: ; Wherein, the catalyst is the catalyst according to any one of claims 1 to 4 or the catalyst obtained by the preparation method according to any one of claims 5 to 8.
10. The synthesis method according to claim 9, characterized in that The catalyst is loaded in a fixed bed, and the temperature of the oxidation reaction is 60-65°C.
Citation Information
Patent Citations
Toluene liquid-phase selective oxidation catalyst and preparation method thereof
CN101972646A
Cerium-vanadium-silicon-titanium composite oxide catalyst and preparation method thereof
CN104148052A
Rare-earth modified sulfur-resisting low-temperature SCR catalyst and preparing method thereof
CN105817220A
Preparation method and application of ternary supported mesoporous silicon ball low-temperature denitration catalyst
CN112264033A
Hydrothermal-aging-resistant low-temperature metal oxide catalyst and preparation method thereof
CN114192138A
Cited By
Thioether oxidation catalyst, preparation method thereof and preparation method of pyroxasulfone
CN120346842A
Sulfide oxidation catalyst, preparation method thereof and preparation method of sulfonepyraclostrobin
CN120346842B
Metal hydroxide catalyst, preparation method thereof and pyroxasulfone synthesis method
CN121648919A